PENGARUH KOMUNIKASI INTERPERSONAL TERHADAP KEMAMPUAN RESOLUSI KONFLIK PADA GEN Z RW 03 JATIWARINGIN - Fauzan Rizki Riswanto; Sari Ekowati (CV Edujavare Publishing, 2026)
This study aims to examine the relationship and influence of interpersonal communication on the conflict resolution abilities of Generation Z in RW03 Jatiwaringin. A descriptive quantitative method with an associative approach was employed. Data were collected via questionnaires distributed to 34 Gen Z respondents selected using purposive sampling. The data were analyzed using the Pearson Product Moment correlation test and simple linear regression analysis via SPSS. The correlation analysis yielded a coefficient (r) of 0.701, indicating a very strong, significant positive relationship between the variables. Furthermore, the coefficient of determination (R²) test revealed that interpersonal communication accounts for 70.1% of the influence on Generation Z's conflict resolution, while the remaining 29.3% is attributed to factors outside the model. Based on the t-test results (8.532 > 2.037) with a significance level of 0.000 < 0.05, it is concluded that interpersonal communication has a significant partial effect on conflict resolution